2019
DOI: 10.3892/etm.2019.8243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicone oil on macular capillary vessel density and thickness

Abstract: The present study assessed changes in macular capillary vessel density and thickness associated with ocular silicone oil tamponade (SOT) following complex vitreoretinal surgery. A total of 23 patients who underwent pars plana vitrectomy combined with intravitreal SOT were retrospectively enrolled, and a single eye was assessed in each participant. Furthermore, 20 patients who required silicone oil removal (SOR) were included. The macular capillary vessel density and the foveal avascular zone (FAZ) area were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
2
12
1
1
Order By: Relevance
“…Here we would also like to include another retrospective study, which included 23 patients with silicone oil tamponade, and reported a decrease in the retinal thickness. 12 This study also included 20 patients in the silicone oil removal group which consequently showed no change in the inner retinal thickness, a finding which is echoed in our study as well. Another study based on 60 silicone oil filled eyes, reported foveal thinning in 30% of the patients after silicone oil tamponade.Surprisingly, this thinning phenomenon was not restricted to the retina alone, but also affected choroid.…”
Section: Resultssupporting
confidence: 76%
“…Here we would also like to include another retrospective study, which included 23 patients with silicone oil tamponade, and reported a decrease in the retinal thickness. 12 This study also included 20 patients in the silicone oil removal group which consequently showed no change in the inner retinal thickness, a finding which is echoed in our study as well. Another study based on 60 silicone oil filled eyes, reported foveal thinning in 30% of the patients after silicone oil tamponade.Surprisingly, this thinning phenomenon was not restricted to the retina alone, but also affected choroid.…”
Section: Resultssupporting
confidence: 76%
“…Consequently, OCTA studies were conducted. So far, OCTA based studies mainly evaluated the impact of SO filling, in which alterations of the microvasculature were present [ 6 , 14 , 15 ]. However, data on the impact of SO removal is limited, and studies on choroidal changes in this context do not exist as far as we know [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endotamponade with SO, as well as its removal from the vitreous cavity are known to impact retinal and choroidal microstructures [ 5 ]. Several studies with different methodological approaches attempted to examine vascular and perfusion alterations due to SO tamponade and its removal [ 6 , 7 , 8 ]. Optical coherence tomography angiography (OCTA) is a non-invasive vascular imaging technique that allows us to look at this question more in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang с соавт. [33] провели исследование, где оценивали состояние центральной зоны сетчатки у 23 пациентов, которым была выполнена PPV в сочетании с силиконовой тампонадой, а также у 20 пациентов, которым требовалось удаление СМ. Средняя продолжительность силиконовой тампонады в группе с удалением СМ составила 5,56 ± 2,17 мес.…”
Section: изменение перфузионных параметров при силиконовой тампонадеunclassified